Additional Data for APTmap (public) - Meier, M; Moody, M; Haley, D; Bagot, P (University of Oxford, 2023)
This is data related to the publication "Large-scale APT Data Mining: Methods and Application to Inform Hydrogen Behaviour". It contains the following: - A csv list of Hash values of the APT experiments used in the study. A dcumentation of these hash values is found in a publication of the IFES technical committee, which can be found here: https://docs.google.com/document/d/e/2PACX-1vQyd3Pc32tS7TjFsiLyjhYlOmqFl_UHPgrkowYIFONIaOYVjmNaiK5HkMIoLurkwP-qzKLLKUXtjU9s/pub - Two APT datasets that can be used as search candidates, as described in the paper. The file format is .pos, and a documentation of this format is found in the Appendix of the book "Atom Probe Microscopy" by Gault, Moody, Cairney, Ringer (ISBN:978-1-4614-3435-1) - A collection of APT reconstructions from Cameca PSM samples (silicon), which can be used to test the data analysis scripts which were used in the paper. The reconstructions are in .epos format (see book above for documentation), and compressed into two .zip archives: straight_fp.zip for straight flight path APT experiments, and reflectron.zip for energy-compensated experiments.